PENGARUH DEWAN KOMISARIS, DEWAN PENGAWAS SYARIAH (DPS) DAN DIREKSI TERHADAP KINERJA MAQASID SYARIAH - Rismayani, Gista; Nanda, Ulfa Luthfia (Jurnal Riset Keuangan dan Akuntansi, 2018)
Sharia Maqasid Performance is the result described from a conceptual framework based on sharia maqasid theory. A maqasid sharia performance should be an effort for Islamic financial institutions to establish a goal that not only profit-oriented but also falah. This study aims to identify factors affecting the sharia maqasid performance of Islamic banking in Indonesia. The dependent variable used in this study is sharia maqasid performance and the independent variables in this study areboard of commissioners performance, Sharia Supervisory Board Performance, and board of directors performance. The study population is sharia banking registered in Bank Indonesia. Using purposive sampling technique obtained 7 islamic banking which become object in this research.The data analysis using panel data regression by Eviews 9. The results indicates that the variables of board of commissioners performance, sharia board performance. and board of directors performance have no significant effect toward the Sharia Maqasid Performance.